Evaluation of an adolescent girl intervention in Rajasthan, India: Pre-analysis plan - Alison Andrew; Sonya Krutikova (Institute for Fiscal Studies (IFS), 2018)
This is a pre-analysis plan specifies analysis we plan to perform for the evaluation of PANKH: an intervention in Dhaulpur district, Rajasthan targeting marriage, education, mental health and socio-emotional skills of adolescent girls as well as gender attitudes of girls and their carers. Given the diverse range of outcomes covered the results of these analyses may be published separately. If we deviate from the methods set out in this document we will provide clear justifications and wherever possible will also publish per-plan analysis for comparison. This study evaluates two models of delivering the PANKH intervention: (i) Girls only model and (ii) Girls + Community model. This is a cluster randomised controlled trial across 90 clusters. Stratifying by the three study blocks we allocated 30 clusters to each to: (i) control, (ii) girls only model, (iii) girls + community model. Full details of interventions and study design are available in the baseline report.
Keywords: 330